2013
DOI: 10.4236/ns.2013.51013
|View full text |Cite
|
Sign up to set email alerts
|

Growth and fatty acid composition of Nile tilapia <i>Oreochromis niloticus</i> L. fed Azolla-diets, in tanks and in earthen ponds: A comparative study

Abstract: Two 90-day experiments were conducted in the same period in tanks and in earthen ponds to study the effects of culture systems on growth and fatty acid (FA) of Nile tilapia (Oreochromis niloticus L.) fingerlings (mean weight: 16.3 g) fed Azolla, as partial replacement for fish meal (FM). Diets were isonitrogenous (29.2% CP) and isoenergetic (16.9 kJ•g −1) containing 0% (A 0), 10% (A 10), 20% (A 20), 30% (A 30), 40% (A 40) and 50% (A 50) of Azolla meal (AM) respectively. Diet A 0 , without AM, acted as a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The results further showed statistically comparable phytoplankton biomass and abundance between the ponds under MI and RB treatments. These findings are in agreement with the results reported by Abou et al (2013) for O. niloticus reared in ponds and fed a plant-based diet ( Azolla spp.). The comparability in composition, biomass and abundance of phytoplankton in the ponds is due to similar diets and fertilization rates used.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results further showed statistically comparable phytoplankton biomass and abundance between the ponds under MI and RB treatments. These findings are in agreement with the results reported by Abou et al (2013) for O. niloticus reared in ponds and fed a plant-based diet ( Azolla spp.). The comparability in composition, biomass and abundance of phytoplankton in the ponds is due to similar diets and fertilization rates used.…”
Section: Discussionsupporting
confidence: 93%
“…Lipids contain more energy per unit weight than protein and carbohydrates (Jauncey 1998), are used efficiently as energy sources (De Silva and Anderson 1995) and are digested and metabolized easily by fish (Doreau and Chilliard 1997). Previous studies have established that, proper nutrient composition of feeds is a primary factor required for survival, muscle development and growth performance of O. niloticus (Abou et al 2013; Valente et al 2013; Ferdous et al 2014; Wijaya et al 2015). Accordingly, the slight differences in protein and lipid between the two diets used ensured similar survival, condition factor and growth of O. niloticus because they balanced their effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro et al (2011) found a greater accumulation of crude protein in tilapia muscle grown in earthen ponds compared with those reared in concrete tanks. Abou et al (2013) observed that O. niloticus receiving the same diet had a higher average final weight in earthen pond cultivation when compared to concrete tank cultivation. As these characteristics relate to muscle growth, it is possible that the availability of natural food in earthen ponds in the present study influenced the higher incidence of hypertrophic growth.…”
Section: Contribution Of Hyperplasia and Hypertrophy To Muscle Growthmentioning
confidence: 80%
“…Concrete tanks and earthen ponds are employed for tilapia culture. Earthen ponds are more advantageous than concrete tanks due to the greater availability of natural feed, which may positively affect performance and other production characteristics (Ribeiro et al, 2011;Abou et al, 2013). This may be related to increased muscle growth and to several other factors related to growth, such as myostatin.…”
Section: Introductionmentioning
confidence: 99%